ANALISIS LIVING QURAN TERHADAP TRADISI SEWELASAN DI PESANTREN AL-MARDLIYYAH TAMBAKBERAS JOMBANG - Muthi'ah Hijriyati (Universitas Hasyim Asy'ari (UNHASY) Tebuireng Jombang, 2020)
Interactions between Holy Koran and humans often experience differences from studies of the interpretation of the Holy Koran itself. People’s responses to the Koran and its practice become a separate phenomenon that deserves to be examined. Because the study of the Koran does not always have to be centered on the study of texts alone, the public response to the Koran can become a new stream of contemporary Koran study research. Considering that the study of ansikh's Koran study cannot capture the social reception of the people of the Koran. The phenomenon of the Koran that